2021
DOI: 10.1098/rsos.202274
|View full text |Cite
|
Sign up to set email alerts
|

Physiological factors influencing female fertility in birds

Abstract: Fertility is fundamental to reproductive success, but not all copulation attempts result in a fertilized embryo. Fertilization failure is especially costly for females, but we still lack a clear understanding of the causes of variation in female fertility across taxa. Birds make a useful model system for fertility research, partly because their large eggs are easily studied outside of the female's body, but also because of the wealth of data available on the reproductive productivity of commercial birds. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 213 publications
(333 reference statements)
0
19
1
Order By: Relevance
“…Thus, regulating lipid metabolism is critical for animal health and welfare, and maintaining egg production and product quality. The lower part of the hen oviduct is open to the cloaca and subject to colonization by various microorganisms via the vagina; this part of the oviduct is more susceptible to infection by microbes (64), resulting in a decrease in lymphocytes and an increase in macrophages during lay. This may negatively affect laying performance and consequently egg quality.…”
Section: Factors Affecting Albumen Quality Animal Healthmentioning
confidence: 99%
“…Thus, regulating lipid metabolism is critical for animal health and welfare, and maintaining egg production and product quality. The lower part of the hen oviduct is open to the cloaca and subject to colonization by various microorganisms via the vagina; this part of the oviduct is more susceptible to infection by microbes (64), resulting in a decrease in lymphocytes and an increase in macrophages during lay. This may negatively affect laying performance and consequently egg quality.…”
Section: Factors Affecting Albumen Quality Animal Healthmentioning
confidence: 99%
“…However, this intervention can have negative impacts, mainly by reducing long-term survival ( Aourir et al, 2013 ; Hampson & Schwitzer, 2016 ; Farquharson, Hogg & Grueber, 2021 ) and introducing behavioural issues ( Utt et al, 2008 ; Jones, 2008 ; Pacheco & Madden, 2021 ) which may cause hand-raised individuals to be unsuited to life in the wild ( Meretsky et al, 2000 ). These behavioural differences appear to affect productivity in some taxa ( King & Mellen, 1994 ; Beck & Power, 1988 ; Hampson & Schwitzer, 2016 ), although the impacts are poorly understood in wild bird species ( Assersohn, Brekke & Hemmings, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Age affects reproductive output in some bird species ( Murgatroyd et al, 2018 ; Brown, Keefer & Songsasen, 2019 ), but not others ( Zhang et al, 2014 ; Fay et al, 2020 ) and in general is poorly studied in wild birds. Mating experience can also affect reproductive output: evidence suggests that both males and females with a greater number of previous breeding attempts may have higher reproductive success ( Kokko, 1997 ; DuVal, 2012 ; Assersohn, Brekke & Hemmings, 2021 ), and so are preferred as mates ( Kokko et al, 1999 ; Jouventin, Lequette & Dobson, 1999 ). Diet is also an important factor in avian reproductive output ( Selman & Houston, 1996 ; Klasing, 1998 ), but this has also not been studied in most wild bird species ( Klasing, 1998 ; Assersohn, Brekke & Hemmings, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fertility is fundamental to reproductive success, so we should expect fertility traits to be under strong selection to maximize reproductive output and minimize the wastage of an animal’s investment in producing gametes. The cost of gametic wastage is likely to be higher for female than male poultry, because females typically invest considerably more into producing yolky ova [ 5 ]. In spite of this, fertility of females has received comparatively less attention than that of males within poultry production.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility varies remarkably between breeds, strains, and individuals and is affected by both genetic and nongenetic factors. Except for sperm quality of the male, several physiological factors originating from the female can markedly influence egg fertilization [ 5 ]. Previous studies have revealed that female birds can store spermatozoa for prolonged periods in the sperm storage tubules [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%